Arbitrarily varying channels with general alphabets and states - Csiszar, I. (IEEE transactions on information theory, 1992)
Previous results of Csiszar and Narayan (1988, 1989, 1991) on the capacity of discrete arbitrarily varying channels with input and state constraints are extended to the case of arbitrary alphabets and state sets. For channels with scalar or vector inputs and additive interference consisting of a deterministic part and noise, both arbitrarily varying subject to power constraints, the capacity for deterministic codes is shown to be equal to the random coding capacity if the input power exceeds the power of the deterministic interference, and zero otherwise. Explicit capacity formulas are also given.< >